Typhus Epidemic in Upper Silesia (1847–1848), as Reported by Doctors (Zaranie Śląskie, 2021)
The article is an attempt to reconstruct and describe a series of dramatic eventswhich took place in Upper Silesia in the times of the typhus outbreak, which ragedacross a few counties in the years 1847–1848. The starting point are the written ac-counts by a group of Upper Silesian doctors, who published a booklet reviewingthe causes and course of the epidemic, as well as fragments from a diary by MaxRing, a doctor and writer residing in the Gliwice County. Both texts offer a medi-cal, social and ethical perspective on the spread of the disease and – importantly– help understand the socio-political relations prevalent in the region, as well asthe relations between the Prussian government, the Berlin metropolis and theprovince-based officials. The report by a Berlin doctor, Rudolf Virchow, assignedby the Ministry of Health to investigate the situation (1848), is an interesting wayto enhance the knowledge of the outbreak, of the regional health service and ofthe difficult, unsolved problems of hygiene, education and social in equalities inUpper Silesia. The article documents – on the one hand – the efforts of local doc-tors to bring relief to the sick and – on the other hand – their commitment to thereform of the health system, whose aim was to provide quality health service to thepoorest group of Upper Silesians.